Osteocalcin is associated with triglyceride glucose index rather than HOMA-IR in men with type 2 diabetes - Huang, Huijie; Wang, Ai; Cong, Li; Zeng, Yingjuan (Frontiers in Endocrinology, 2022)
Introduction: The involvement of osteocalcin in the regulation of glucose tolerance in humans is controversial. We utilized a novel and practical insulin resistance surrogate, the triglyceride-glucose (TyG) index, to investigate the association between serum osteocalcin and insulin resistance in men with type 2 diabetes (T2D). Methods: This was a retrospective cross-sectional study that included 667 male patients suffering from T2D, with measurements of N-terminal mid-fragment of osteocalcin (N-MID), triglycerides (TG), fasting blood glucose (FBG) and C-peptide collected on the same day. We used the TyG index and HOMA-IR as surrogate measures for insulin resistance. Binary logistic regression models that adjust the sociodemographic characteristics and metabolism-related factors were used to assess the associations between osteocalcin and insulin resistance. Restricted cubic spline (RCS) analysis was used to test the potential non-linear relationship between N-MID and the risk of severe insulin resistance. Subgroup analysis evaluated the robustness of the association. Results: N-MID was correlated with the level of insulin resistance when quantified by the TyG index in unadjusted and adjusted binary logistic regression models (all p < 0.05), but the relationship was not observed when assessed by HOMA-IR (all p > 0.05). RCS model further confirmed that the association between N-MID and the severe insulin resistance measured by the TyG index was non-linear (P = 0.047). Subgroup analysis showed that the association was detected only in younger patients with lower BMI and poorer glycemic control, without hypertension or smoking.